2010
DOI: 10.1016/j.homp.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The similia principle: Results obtained in a cellular model system

Abstract: This paper describes the results of a research program focused on the beneficial effect of low dose stress conditions that were applied according to the similia principle to cells previously disturbed by more severe stress conditions. In first instance, we discuss criteria for research on the similia principle at the cellular level. Then, the homologous ('isopathic') approach is reviewed, in which the initial (high dose) stress used to disturb cellular physiology and the subsequent (low dose) stress are identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…This study was based on the work done by Van Wijk [7] and Wiegant [8] who described how self-recovery at the organ level showed a shift of symptom picture over time; a toxin entered a system, damaged an organ, the organ began to regenerate and eliminated the toxin, which then affected a different organ and led to complications with a wide variety in the symptoms over time. It was noted that self-recovery at the cellular and molecular levels had no issue with the above time shift of symptoms [2].…”
Section: Introductionmentioning
confidence: 99%
“…This study was based on the work done by Van Wijk [7] and Wiegant [8] who described how self-recovery at the organ level showed a shift of symptom picture over time; a toxin entered a system, damaged an organ, the organ began to regenerate and eliminated the toxin, which then affected a different organ and led to complications with a wide variety in the symptoms over time. It was noted that self-recovery at the cellular and molecular levels had no issue with the above time shift of symptoms [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous empirical studies have shown that different homeopathic remedies modulate components of the allostatic stress response network. These findings include remedy-induced changes in heat shock proteins [7,17,146], cytokines [147-149], immune [150-153], metabolic [12,131], and nervous system [154-162] function, as well as gene expression patterns [9,163,164]. Nanoparticles per se can and do mobilize components of the allostatic network [165-167].…”
Section: Discussionmentioning
confidence: 99%
“…Basic science research suggests that classically-prepared homeopathic remedies (A) contain measurable source nanoparticles (NPs) and/or silica nanoparticles with adsorbed source materials [1-4] which are heterogeneously dispersed in colloidal solution; (B) act by modulating biological function of the allostatic stress response network [5,6], including cytokines, oxidative stress and heat shock proteins [7,8], as well as immune, endocrine, metabolic, autonomic and central nervous system functions [9,10]; (C) evoke biphasic actions on the adaptive plasticity of living systems [11-15] via organism-dependent, endogenously amplified, rather than agent-dependent pharmacological, effects [16]. The effects of homeopathic remedy nanoparticles involve state- and time-dependent adaptive changes [7,8,17-20] within the complex adaptive organism [19-22]. The main clinical outcome is (D) improvement in systemic resilience to future environmental stressors and recovery back to normal healthy homeostatic functioning [23].…”
Section: Introductionmentioning
confidence: 99%
“…Homeopathic aggravation is a basic element of homeopathy, not only at the clinical level, but is also observed at the cellular level, in terms of enhanced stress protein production, as some in vitro studies have demonstrated recently. 19 Some studies report that the frequency of aggravation using centesimal potencies is 30.8% in the first 6 months of Aggravation with Q potencies treatment, 20 25.4% mild and 7.8% more severe. 21 In randomized placebo controlled trials, which included a total of 305 patients, 50 cases of homeopathic aggravation were reported (16.4%).…”
Section: Discussionmentioning
confidence: 99%